Garden City lamb feeding experiments - Hillman, M.; Erhart, A.B.; Menzies, C. (Kansas Agricultural Experiment Station, 2011)
The 638 white-face feeder lambs used in these tests were received October 18, 1961, at the Zuni Indian Reservation south of Gallup, N.M. Average purchase weight was 71.2 lbs. per head. They arrived in Garden City, October 20, and weighed 64.1 lbs. per head off the cars.
Keywords: Sheep; Feed efficiency; Gain; Protein